Evidence–based practice at the centre of paradigm shift in social work? - Vučinić Jovanović, Marija; Hrnčić, Jasna; Gajić, Miona (Sociološki pregled, 2024)
Evidence-based practice in social work elicits a broad spectrum of reactions which reflect the dynamics of modern and postmodern approaches, where the traditional emphasis on empirical methods and objectivity confronts the challenges of postmodern skepticism and relativism. Drawing on Thomas Kuhn’s model of scientific development as a theoretical-analytical framework, this paper aims to analyze the debate between modern and postmodern approaches regarding evidence-based practice in social work. Using the methods of content analysis, comparative and narrative analysis, as well as synthesis, the paper focuses on the current debate as an expression of the crisis and conflict between these two paradigms, considering their fundamental ontological, epistemological, methodological, and axiological assumptions. The development of evidence-based practice through the succession of stages of normal science and crisis is presented, followed by the discussion of the main modernist and postmodernist arguments. This opens up the question of the implications of this conflict on the application and the further development of the evidence-based practice approach in social work. It is concluded that, despite the apparent irreconcilability of these approaches, their critical interaction, illuminated through Kuhn’s ideas on scientific paradigms, plays a key role in the development of evidence-based practice.
Keywords: social work; paradigm; modernism; postmodernism; evidence-based practice (EBP)